Practical Applications in Biomedical Engineering - Andrade, Adriano O.; Alves Pereira, Adriano; Naves, Eduardo L. M.; Soares, Alcimar B. (IntechOpen, 2013)
Biomedical Engineering is an exciting and emerging interdisciplinary field that combines engineering with life sciences. The relevance of this area can be perceived in our everyday lives every time we go to hospital, receive medical treatment or even when we buy health products such as an automatic blood pressure monitor device. Over the past years we have experienced a great technological development in health care and this is due to the joint work of engineers, mathematicians, physicians, computer scientists and many other professionals. This book introduces a collection of papers organized into three sections that provide state of the art examples of practical applications in Biomedical Engineering in the area of Biomedical Signal Processing and Modelling, Biomaterials and Prosthetic Devices, and Biomedical Image Processing.